2019
DOI: 10.1111/ele.13425
|View full text |Cite
|
Sign up to set email alerts
|

The spatial frequency of climatic conditions affects niche composition and functional diversity of species assemblages: the case of Angiosperms

Abstract: Climatic conditions vary in spatial frequency globally. Spatially rare climatic conditions provide fewer suitable environments than common ones and should impose constraints on the types of species present locally and regionally. We used data on 467 North American angiosperms to test the effects of the spatial frequency of climatic conditions on ecological niche specialisation and functional diversity. We predicted that rare climates should favour generalist species that are able to inhabit a broader range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…We also note that the spatial resolutions of a number of the remotely sensed environmental layers used in this study (SI: File 4) may not be fine enough to sufficiently capture their influence in a highly heterogeneous urban environment. For example, while urban areas tend to produce highly localized microclimates which influence local patterns of biodiversity (Fournier et al 2020;Casanelles-Abella et al 2021), the resolution the bioclimatic variables we used are near a kilometer in scale and may effectively obscure the data on land cover and vegetation found to support native biodiversity in Los Angeles, along with a measure of geographic connectivity between habitats supportive of native biodiversity (Brown, 2019). That our two SRMs both predict a positive relationship between HabitatQuality and species richness (SI: Figures 6j and 7b) is not surprising, with urban species richness generally found to increase with related metrics such as the area or connectivity of vegetated habitats (Aronson et al 2014;Beninde et al 2015;Callaghan et al 2018).…”
Section: Selecting Environmental Indicator Speciesmentioning
confidence: 99%
“…We also note that the spatial resolutions of a number of the remotely sensed environmental layers used in this study (SI: File 4) may not be fine enough to sufficiently capture their influence in a highly heterogeneous urban environment. For example, while urban areas tend to produce highly localized microclimates which influence local patterns of biodiversity (Fournier et al 2020;Casanelles-Abella et al 2021), the resolution the bioclimatic variables we used are near a kilometer in scale and may effectively obscure the data on land cover and vegetation found to support native biodiversity in Los Angeles, along with a measure of geographic connectivity between habitats supportive of native biodiversity (Brown, 2019). That our two SRMs both predict a positive relationship between HabitatQuality and species richness (SI: Figures 6j and 7b) is not surprising, with urban species richness generally found to increase with related metrics such as the area or connectivity of vegetated habitats (Aronson et al 2014;Beninde et al 2015;Callaghan et al 2018).…”
Section: Selecting Environmental Indicator Speciesmentioning
confidence: 99%
“…Climate (i.e., mean and variation across space and time) drives the past and current distribution of biodiversity (Fournier et al, 2020; Mittelbach et al, 2007; Stein et al, 2014). We also observed that elevational variation in climate is the main factor explaining the distribution of fireflies along the focal tropical slope (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Abiotic stressors shape biodiversity by filtering from ecological community subsets of species whose traits are not in equilibrium with local habitat conditions (Fournier et al, 2020; Kraft et al, 2015; McGill et al, 2006). Consequently, the non‐random distribution of traits and life history syndromes along environmental gradients of natural stressors (e.g., climate, fire disturbance and soil composition) is a ubiquitous pattern in nature (Cornwell & Ackerly, 2009; Gutiérrez‐Cánovas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Local species richness patterns reflect the influences of environmental attributes on species coexistence and population distributions (Allouche et al 2012, Frid et al 2018, Gong et al 2019, Liu et al 2019). Many previous studies have tested the effects of environmental heterogeneity and homogeneity on species richness, and showed that heterogeneity can enhance species richness by allowing the coexistence of more species with different niches (Mellard et al 2012, Stein et al 2014, Mandal et al 2018, Fournier et al 2020). However, the advantages of heterogeneity often come at the costs of smaller habitat areas and higher impairments to movement and dispersal, which conversely increase local extinctions and decrease richness (Nogues‐Bravo et al 2008, Allouche et al 2012, He 2012, Hart et al 2017, Fournier et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Because the two metrics of heterogeneity and habitat area (i.e. the number of habitat types and the area of each habitat, respectively) effectively capture different aspects of environmental and spatial influences on species richness (Allouche et al 2012, Frid et al 2018, Fournier et al 2020), balancing these two metrics is crucial to understand, predict and conserve species richness.…”
Section: Introductionmentioning
confidence: 99%